The synergy between human factors and risk attitudes of Malaysian contractors’: Moderating effect of government policy - Taofeeq, D. M.; Adeleke, A. Q.; Lee, Chia Kuang (Elsevier Ltd, 2020)
Many critical factors influence the effectiveness of risk management. There is unanimity among project and risk practitioners about the most significant factor responsible for risk management: “human factors”. As human attitude is always reflected in behaviour, there is a high possibility that a contractor's behaviour will be by the attitude. Therefore, this study aims to identify the factors affecting contractors' risk attitudes and then determine the relationship with government policy. A total of 100 copies of questionnaire were randomly distributed to the construction companies in Kuantan Malaysia. Out of the 100 copies of the questionnaire distributed, 69 copies were received indicating 72.6% response rate. Thirteen (13) copies of the questionnaire were found to be unusable due to missing data or errors in the responses to all the questions. Thus, 56 copies of the questionnaire, indicating 58.9% response rate, were usable. Moreover, with quantitative research design following the positivist research paradigm, the methodology was designed to focus on the research questions and the objectives. Organizational Control Theory was used to develop the theoretical framework that investigated G-7 contractors in the Kuantan Pahang, Malaysian construction companies. SPSS 20.0 & SmartPLS 3 for structural equation modelling was utilized in testing the hypotheses developed for the study. Government policy moderates the relationships between the internal factors and contractors' risk attitudes among the construction companies operating in Kuantan, Malaysia. This implies that the findings of the study provides more understanding of the personal factors that affect contractors' risk attitudes to facilitate contractors' decision-making process. It also serves as a useful reference for further studies in the field of construction project management.